2006
DOI: 10.1002/ajim.20340
|View full text |Cite
|
Sign up to set email alerts
|

Worker productivity and outpatient service use after the September 11th attacks: Results from the New York City Terrorism Outcome Study

Abstract: This study suggests that while the WTCD had an impact on worker productivity within the first year after the attack, this did not generally persist, especially after controlling for baseline status. Having PTSD or experiencing stressful life events at follow-up, however, is associated with lower quality workdays, even after controlling for baseline status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…To have PTSD, the person had to meet criteria A through F for one or more of these traumatic events in the past 12 months. Data supporting the validity of this instrument have been presented elsewhere and suggested that this scale can successfully diagnose PTSD in the general population (Boscarino et al, 2004a,b; Adams and Boscarino, 2005b, 2006; Boscarino et al, 2006a,b,c). For the current analyses we so defined PTSD as present if the respondent had subclinical or partial PTSD at follow-up.…”
Section: Methodsmentioning
confidence: 70%
See 3 more Smart Citations
“…To have PTSD, the person had to meet criteria A through F for one or more of these traumatic events in the past 12 months. Data supporting the validity of this instrument have been presented elsewhere and suggested that this scale can successfully diagnose PTSD in the general population (Boscarino et al, 2004a,b; Adams and Boscarino, 2005b, 2006; Boscarino et al, 2006a,b,c). For the current analyses we so defined PTSD as present if the respondent had subclinical or partial PTSD at follow-up.…”
Section: Methodsmentioning
confidence: 70%
“…The combined mean lifetime trauma exposure at follow-up was 1.9 (SD = 2.5). All three of these stressor measures were used and validated in previous WTCD studies and discussed in detail elsewhere (Galea et al, 2002; Boscarino et al, 2004a, b; Adams and Boscarino, 2005a,b; Adams et al, 2006a; Boscarino et al, 2006b,c). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study from New York showed significant association of PTSD with low quality of work days in people who witnessed the world trade center incident. [26] Detroit survey of trauma reports significant work loss of 11.4 (SE 0.6) days per capita in people with PTSD [10] and 2.4 (SE 1.06) days in full time workers from Australia. [27] These statistics reflect considerable variation in emotional reaction of stress on job performance.…”
Section: Discussionmentioning
confidence: 99%